HELMINTH FAUNA OF PEPRILUS SNYDERI GILBERT & STARKS, 1904 (STROMATEIDAE) OF CHORRILLOS FISHMARKET, LIMA, PERÚ - Ñacari, Luis (2014)
With the aim of know the Helminth fauna of Peprilus snyderi (Gilbert & Starks, 1904) (Stromateidae), a demersal fish carnivore in the central coast of Peru, were examined 214 samples of P. snyderi from the Chorrillos Fishmarket, collected during the months of February 2011 to February 2012. We found nine species of helminths. Monogenea: Oaxacotyle oaxacensis, Digenea: Lecithocladium cristatum, Opechona pharyngodactyla, Lepidapedon sp1, Lepidapedon sp2 and Lepidapedon sp3, Nematoda: Hysterothylacium sp (Larvae), Anisakis sp. (Larvae L3) and Rusguniella sp. (Larvae). Opechona pharyngodactyla, Lepidapedon sp1, Lepidapedon sp2, Lepidapedon sp3 and Rusguniella sp. (Larva) are new records for Peru.